IMPACT OF ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Mafrudoh, Mafrudoh (Laboratorium Riset Ekonomi, 2023)
Purpose: If you look at the big picture a society’s culture determines how people behave, respond, and interact with one another and how fast the society can grow as a community. This definition holds true for organizational culture too. The purpose of this research is to find out the impact of organizational culture on employee performance, how engaged employees are at work depends on how happy and comfortable they feel about the organizational culture. Methodology: The method used in this article is a qualitative method, where we describe how organizational culture affects employee performance. The data collection technique is done by observation through articles available on trusted journal pages. Findings: The goal of an organization is to increase level of performance by designing strategies. Based on the results of data analysis, organizational culture helps retain top performance and valuable talent. It creates a culture of engagement and increases employee productivity It makes people happy and excited about the workplace. How culture affects employee engagement about 87% of organizations agree that employee engagement and culture are the two most vital workplace challenges.